Prevalence of endometriosis in women undergoing laparoscopic surgery for various gynecological indications: a Jordanian multi-center retrospective study - Mohammad Al-Jafari; Marah Ahmad Aldarawsheh; Mohamed Abouzid; Ibrahim Serag; Mariam Akram Nofal; Ammar Ra’ed Altiti; Saja Zuaiter; Aya Sabri Al-Zurgan; Basil Aldiabat; Julie Feras Owaidat; Sadeen Zein Eddin; Wedad Ahmad Sawas; et al. (BMC Women's Health)
Abstract Background Endometriosis, a condition that significantly impacts the quality of life for affected women, manifests with a spectrum of symptoms ranging from mild discomfort to severe pelvic pain, dysmenorrhea, dyspareunia, and infertility. A previous single-center study suggested an elevated prevalence of endometriosis in Jordan, prompting the need for larger studies to confirm these findings. Methods We conducted a cross-sectional study involving a sample of 866 women who underwent various laparoscopic procedures for different indications at the Department of Obstetrics and Gynecology at Jordan University Hospital and Al-Karak Governmental Hospital, two tertiary referral hospitals in Jordan between January 2015 and March 2023. Results Our study included 866 patients who underwent gynecological laparoscopic surgery between 2015 and 2023, with a mean age of 33.80 ± 7.7 years. Of these, 89 women were diagnosed with endometriosis, resulting in an overall prevalence of 10.3%. Diagnostic laparoscopy was the most common procedure, performed on 28.4% of patients. Infertility was the most common indication, observed in 34.5% of patients. Endometriosis was significantly more prevalent in patients with chronic pelvic pain (29.7%) and less prevalent in those seeking treatment for infertility (13.8%), ectopic pregnancy (1.1%), and family planning (0%). Endometriosis was significantly less prevalent in patients undergoing laparoscopic salpingectomy or salpingostomy (3.7%). Backstep-wise multivariate regression analysis suggested that endometriosis may be associated with higher age (OR 1.04, 95%CI 1.00 to 1.07, p = 0.027), lower BMI (OR 0.92, 95%CI 0.87 to 0.98, p = 0.007), lower number of parities (OR 0.72, 95%CI 0.6 to 0.86, p < 0.001), and fewer cesarean sections (OR 0.53, 95%CI 0.32 to 0.87, p = 0.013). Conclusion This is the most extensive Jordanian study assessing the prevalence of endometriosis in women undergoing gynecological laparoscopy. Our results suggest that the prevalence of endometriosis among Jordanian women remains high, albeit lower than previously reported. The study uncovered that age, BMI, parity number, and cesarean sections are predictors of endometriosis. Future research may explore causative reasons for the higher prevalence of endometriosis and the influence of other comorbidities, medications, and lifestyle factors.